Qualidade e produtividade da cana planta e cana soca em função de doses e fontes de manganês - Benett, Cleiton Gredson Sabin; Buzetti, Salatiér [UNESP]; Silva, Katiane Santiago; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Maeda, Alexandra Sanae; Garcia, Cássia Maria de Paula [UNESP] (My University, 2012)
The crop of the sugarcane is stood out in the Brazilian agricultural scenery, due to the great demand of sugar, alcohol and by-products. The present work had as objective to evaluate the effect of five doses and three sources of manganese applied at planting furrow in sugarcane, in two cuts, in the Northwest area of São Paulo State, Brazil. The experiment was conducted at Fujimoto farm with coordinates 20 ° 32 'S and 50 ° 58' O, and altitude of 361 meters, area administered by Distillery Vale do Paraná S/A Álcool and Açúcar, in Suzanápolis county – São Paulo state. A randomizef blocks design in a factorial scheme 5x3, being 5 doses of manganese (0; 2.5; 5.0; 7.5 and 10.0 kg ha-1), and 3 sources (Quelate, FTE and manganese sulfate), applied at planting furrow, in 4 repetitions was used. The plots were constituted by 4 lines of 5 m length, spaced by 1.5 m. The RB 86-7515 variety was used. The sources of manganese did not influence in the technological quality and productivity of stems in none of the cuts of sugarcane. The application of doses of manganese resulted in increase on values of recoverable total sugar per ha and ton of pol per ha in plant cane, not influencing in the other variables analyzed on plant cane and ratoon cane.
Quality and productivity of plant cane and ratoon cane to levels and sources of manganese
Keywords: Manuring; Micronutriente; Saccharum spp; Sucrose